GUIDED INQUIRY MODEL THROUGH VIRTUAL LABORATORY TO ENHANCE STUDENTS' SCIENCE PROCESS SKILLS ON HEAT CONCEPT - Gunawan Gunawan; Ahmad Harjono; Hermansyah Hermansyah; Lovy Herayanti (LPMPP Universitas Negeri Yogyakarta, 2019)
Science process skills are one of the indicators to know the level of achievement of physics teaching goals. This research examines the influence of guided inquiry models through virtual laboratories on students' science process skills. The research was a quasi-experiment conducted at the senior high school in Mataram, Lombok. The samples were class XI students, as many as 58 people divided into two sample groups: experimental and control groups. The guided inquiry model through the virtual laboratory was applied to the experimental group and the conventional model for the control group. The instrument used was a performance sheet. A t-test was used to analyze the effect of learning model on science process skill. The results of this study found that the achievement of science process skills for the experimental group was higher than the control group. The guided inquiry models through virtual laboratory have a significant effect on science process skills, especially on skills: hypothesizing, practicing, and communicating. These findings contribute significantly to the current knowledge about the effectiveness of guided inquiry models through virtual laboratories to improve students' science process skills in physics teaching.